The cardiovascular changes underlying a low cardiac output with exercise in patients with type 2 diabetes mellitus - Lav Madsen, Per; Sejersen, Casper; Nyberg, Michael; Sørensen, Martin Heyn; Hellsten, Ylva; Gaede, Peter; Bojer, Annemie Stege (Frontiers in Physiology, 2024)
The significant morbidity and premature mortality of type 2 diabetes mellitus (T2DM) is largely associated with its cardiovascular consequences. Focus has long been on the arterial atheromatosis of DM giving rise to early stroke and myocardial infarctions, whereas less attention has been given to its non-ischemic cardiovascular consequences. Irrespective of ischemic changes, T2DM is associated with heart failure (HF) most commonly with preserved ejection fraction (HFpEF). Largely due to increasing population ages, hypertension, obesity and T2DM, HFpEF is becoming the most prevalent form of HF. Unfortunately, randomized controlled trials of HFpEF have largely been futile, and it now seems logical to address the important different phenotypes of HFpEF to understand their underlying pathophysiology. In the early phases, HFpEF is associated with a significantly impaired ability to increase cardiac output with exercise.The lowered cardiac output with exercise results from both cardiac and peripheral causes. T2DM is associated with left ventricular (LV) diastolic dysfunction based on LV hypertrophy with myocardial disperse fibrosis and significantly impaired ability for myocardial blood flow increments with exercise. T2DM is also associated with impaired ability for skeletal muscle vasodilation during exercise, and as is the case in the myocardium, such changes may be related to vascular rarefaction. The present review discusses the underlying phenotypical changes of the heart and peripheral vascular system and their importance for an adequate increase in cardiac output. Since many of the described cardiovascular changes with T2DM must be considered difficult to change if fully developed, it is suggested that patients with T2DM are early evaluated with respect to their cardiovascular compromise.